Warm and cold events in the tropical eastern Atlantic off Angola - MACUÉRIA, Marisa Francisca de Novato (2019)
Upwelling occurs along large portions of the Angola's coast enhancing biological productivity with positive reflex to local economy and food security. To investigate the occurrence of warm and cold events off the Angolan coast (006º-018ºS) 9,529 vertical profiles of temperature, salinity and dissolved oxygen collected during 1995-2016 in the austral summer (Feb-Apr) and winter (Jul-Aug) under the EAF-Nansen Program were analysed. The dataset was classified according to the occurrence of warm (Benguela Niño), cold (Benguela Niña) and neutral (normal) Sea Surface Temperature anomalies for each season. A strong seasonality in near surface temperature and salinity was detected. During austral summer the ocean off Angola is fresh and warm, while during austral winter it is saltier and colder. However extreme events Benguela Niño and Niña are more likely to occur during austral summer. Benguela Niño is marked by a poleward intrusion of warm equatorial water and by reduced upwelling. Results showed the strong influence of the Angola Current warm waters being transport southward. Low salinity waters (34) were observed associated to abnormally high river discharges (Congo and Kwanza) and direct precipitation that appears contribute to the development of warm events by enhancing the stratification. A maximum salinity value (35.8) was observed in the Angola-Benguela Front region while in the open sea salinity remained in the range of 35 along the entire platform. During Benguela Niña events cold and salty water masses were verified along the coast. Cold waters from the Benguela Current move northwards and reach Lobito (12°S). In the northern (6º-9°05’S) and central region (9°05’-13°S) temperature ranged from 21-24°C and at the south region (13-18°S) from 14° to 20°C. Salinity values along the coast ranged from 35.6 to 35.8 except in the area under the influence of the discharges of the Congo River. One of the world’s most pronounced oxygen minimum zone (OMZ) is found below the productive surface layer of the Angola’s Sea. Dissolved oxygen (DO) concentrations along the coast of Angola are in general lower during austral winter than during austral summer and much lower during normal and Benguela Niña years relative to Benguela Niño years. During the austral summer DO concentrations varies from 1.5 to 4.0 mL.L-1 in normal, 2 to 3 mL.L-1 in Benguela Niño years and 0.0 to 1.5 mL.L-1 in Benguela Niña years. During austral winter DO varied from 2 to 3.5 mL.L-1 in normal (except at 7°S where small lenses of the OMZ reached the coast) and 2-3 mL.L-1 in Benguela Niño years. In the years of Benguela Niña the OMZ is spread offshore reaching ~7ºS. Along the coast, the DO ranged from 1.5 to 3 mL.L-1, reaching 3.5 mL.L-1 between 6º and 7º13’S.